BIG DATA: A SOURCE OF COMPETITIVE ADVANTAGE - Rusu, Bianca; Hurloiu, Lacramioara; Hurloiu, Iulian; Geamanu, Marinela (Annals of Spiru Haret University. Economic Series, 2022)
In a business environment that constantly and rapidly changes, future prediction becomes more important than the simple visualization of historical or current perspectives. For effective future prediction, data analysis using statistical and predictive modelling techniques may be applied to enhance and support the organization’s business strategy. Therefore, the effective use of data is becoming the basis of competition. Big data fundamentally change the way businesses compete and operate. Companies that invest in and successfully derive value from their data have a distinct advantage over their competitors. This performance gap will continue to grow as more relevant data is generated and the technologies that enable faster, easier data analysis continue to develop.